Aneurysm Regression after Coil Embolization of a Concurrent Aneurysm - Chow, Michael M.; Thorell, William E.; Rasmussen, Peter A. (American Journal of Neuroradiology, 2005)
Summary: A 43-year-old woman with two incidental paraclinoid internal carotid artery aneurysms underwent coil embolization of the larger superior hypophyseal aneurysm and 10 weeks later underwent follow-up angiography that showed regression of the smaller, more distal paraclinoid aneurysm. We demonstrate that, although it is a rare occurrence, aneurysms can involute. We discuss potential mechanisms of this phenomenon and review the literature on aneurysm regression.